2019
DOI: 10.1002/aelm.201800740
|View full text |Cite
|
Sign up to set email alerts
|

Designed Memristor Circuit for Self‐Limited Analog Switching and its Application to a Memristive Neural Network

Abstract: Self-limited switching is a technique that can control the memristor resistance up to a specific value by limiting excessive switching. [14,15] For example, in self-limited "set" switching, a series resistor (R S ) is connected to a memristor (M). The R S -M configuration is biased with a programming voltage (V P ) to switch the M from the HRS to the LRS. Before the switching happens, if the node voltage on M is V M , the V M is almost equal to the V P because the R HRS is much larger than the resistance of R … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…However, the development of energy-efficient neuromorphic hardware systems has been hindered by the limited performance of analogue synaptic devices . A specific memristor circuit was typically designed in order to achieve self-limited analogue switching, and thus its application to a memristive neural network . Analogue programming can provide the synapses with both analogue depression and potentiation by accurately controlling intermediate states.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the development of energy-efficient neuromorphic hardware systems has been hindered by the limited performance of analogue synaptic devices . A specific memristor circuit was typically designed in order to achieve self-limited analogue switching, and thus its application to a memristive neural network . Analogue programming can provide the synapses with both analogue depression and potentiation by accurately controlling intermediate states.…”
Section: Introductionmentioning
confidence: 99%
“…33 A specific memristor circuit was typically designed in order to achieve self-limited analogue switching, and thus its application to a memristive neural network. 34 Analogue programming can provide the synapses with both analogue depression and potentiation by accurately controlling intermediate states. However, it is at the expense of an increased device fabrication complexity, and such accurate control is difficult because of the inherent stochastic characteristics of the resistance switching.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In fact, researchers have used alternative techniques to design memristor devices based on mathematical models. Analog circuit implementation of memristors is important, and there are many different implementations [ 20 , 21 , 22 , 23 ]. Meanwhile, FPGA implementation has aroused much interest among researchers due to its easily programmable, reconfigurable, controllable, precise and better performance [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another critical issue is the involvement of the random variation in the device characteristics between the cells and switching operations, which certainly impacts the performance of the network. , Such variations can be quantified by adopting a coefficient of variation (CV) that defines the ratio of the standard deviation (σ) to the mean value (μ). Song et al reported recently that CV of about ∼2% does not impact the system performance, demonstrating the defect-tolerant feature of the artificial neural network . In addition to these synaptic performances, conventional memory performance indicators, such as the retention and endurance of the memory cell, are still the crucial factors for the memristor to have in the neural network. Most of the MIM-structured memristors are highly insulating at the as-fabricated state, which requires an electroforming (EF) step to operate them as a feasible memory or synapse.…”
Section: Introductionmentioning
confidence: 99%
“…reported recently that CV of about ∼2% does not impact the system performance, demonstrating the defect-tolerant feature of the artificial neural network. 22 In addition to these synaptic performances, conventional memory performance indicators, such as the retention and endurance of the memory cell, are still the crucial factors for the memristor to have in the neural network. 23−29 Most of the MIM-structured memristors are highly insulating at the as-fabricated state, which requires an electroforming (EF) step to operate them as a feasible memory or synapse.…”
Section: Introductionmentioning
confidence: 99%